Transmission Electron Microscopy Diffraction, Imaging, and Spectrometry - Carter, C. Barry; Williams, David B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This text is a companion volume to Transmission Electron Microscopy: A Textbook for Materials Science by Williams and Carter. The aim is to extend the discussion of certain topics that are either rapidly changing at this time or that would benefit from more detailed discussion than space allowed in the primary text. World-renowned researchers have contributed chapters in their area of expertise, and the editors have carefully prepared these chapters to provide a uniform tone and treatment for this exciting material. The book features an unparalleled collection of color figures showcasing the quality and variety of chemical data that can be obtained from today's instruments, as well as key pitfalls to avoid. As with the previous TEM text, each chapter contains two sets of questions, one for self assessment and a second more suitable for homework assignments. Throughout the book, the style follows that of Williams & Carter even when the subject matter becomes challenging-the aim is always to make the topic understandable by first-year graduate students and others who are working in the field of Materials Science. Topics covered include sources, in-situ experiments, electron diffraction, Digital Micrograph, waves and holography, focal-series reconstruction and direct methods, STEM and tomography, energy-filtered TEM (EFTEM) imaging, and spectrum imaging. The range and depth of material makes this companion volume essential reading for the budding microscopist and a key reference for practicing researchers using these and related techniques. Praise for Transmission Electron Microscopy: A Textbook for Materials Science by Williams and Carter: "The best textbook for this audience available." - American Scientist "...highly readable, and an extremely valuable text for all users of the TEM at every level. Treat yourself to a copy!" - Microscopy and Microanalysis "This book is written in such a comprehensive manner that it is understandable to all people who are trained in physical science and it will be useful both for the expert as well as the student." - Micron "The book answers nearly any question - be it instrumental, practical, or theoretical - either directly or with an appropriate reference...This book provides a basic, clear-cut presentation of how transmission electron microscopes should be used and of how this depends specifically on one's specific undergoing project." - MRS Bulletin "It is truly a book so thoughtfully written that ... it will provide a solid foundation for those studying material science....an outstanding book." - IEEE Electrical Insulation Magazine, Vol. 26 (4), July/August, 2010.
Foreword by Sir John Meurig Thomas -- 1. Electron Sources -- 2. In Situ and Operando -- 3. Electron Diffraction and Phase Identification -- 4. Convergent-Beam Diffraction: Symmetry and Large-Angle Patterns -- 5. Electron crystallography, charge-density mapping and nanodiffraction -- 6. Digital Micrograph -- 7. Electron waves, interference & coherence -- 8. Electron Holography -- 9. Focal-Series Reconstruction -- 10. Direct Methods For Image Interpretation -- 11. Imaging in the STEM -- 12. Electron Tomography -- 13. Energy-Filtered Transmission Electron Microscopy -- 14. Calculation of Electron Energy-Loss Spectra -- 15. Electron Diffraction & X-Ray Excitation -- 16. X-Ray and Electron Energy-Loss Spectral Imaging -- 17. Practical Aspects and Advanced Applications of XEDS.
Keywords: Materials -- Analysis; Nanoscience; Spectrum analysis; Condensed matter; Mechanics, Applied; Solids; Characterization and Analytical Technique; Nanophysics; Spectroscopy; Condensed Matter Physics; Solid Mechanics